At love's bidding [large type] - Jennings, Regina (Regina Lea) (Thorndike Press large print Christian romance series., 2016)
"In 1873, when Boston native Miranda Wimplegate mistakenly auctions off a prized portrait, her grandfather purchases the entire Missouri Ozarks auction house where it was sent. After traveling to the Ozarks to recover it, they make surprising discoveries about their new business"--